Effect of Temperature on Maximum Power Point of Photovoltaic Module (International Journal of Engineering and Computer Science, 2015)
The voltage output and the maximum power point are found to drop with high irradiance and the associated high solar cell surface temperature. The rise in temperature produces thermal agitation which not only increases the dark current but also enhances the losses of free carriers in a PV cell. A number of PV cells have been assembled locally into PV module and experimentally investigated. To control the temperature of the PV module, a cooling chamber (refrigerator) was used. Experiments were performed with and without the cooling chamber. The maximum power point was found to drop with increasing surface temperature. The experiments were carried out and data collected with and without the cooling chamber. In comparison, the surface temperature of the PV module without cooling was found to be higher. However, operation with the cooled chamber recorded a drop in the PV module temperature and in the maximum power point. The study has led to the inference that maximum power point and the output power decrease with an increasing PV cell temperature.